DEVELOPMENT OF CREATIVE APPROACH COMPETENCE IN ORGANIZING ACTIVITIES OUTSIDE THE CLASSROOM IN FUTURE STUDENTS - Nargiza Esenbayevna Perdeshova (Web of Journals Publishing, 2024)
In this article, the results of the experimental test on the development of creative competence of future teachers, the qualities of personal creativity, the factors and ways of developing creative competence, and the methods and strategies of creative teaching will be explained.
Keywords: Future teacher, experimental work, creative competence, qualities of creativity, creative methods and strategies.